Reliability of measurements on lateral ankle radiographs. Issue 1 (December 2016) - Guo, Changjun; Zhu, Yuan; Hu, Mu; Deng, Lianfu; Xu, Xiangyang
Abstract Background The aims of our study were to evaluate the validation of measurement of weight-bearing lateral radiographs. Two hypotheses were tested: the measurements on the lateral radiographs are reliable, and a theoretical limit could be identified when a surgeon can "eyeball" an incongruous ankle joint on lateral radiographs. Methods To test the first hypothesis, 3 experienced ankle surgeons evaluated 50 normal weight-bearing lateral radiographs of patients. The measurements assessed were the tibial lateral surface angle (TLS), the distance from the center of the talar joint circle to the longitudinal axis of the tibia (x) and the displacement from the center of the talar articular joint circle to the center of the distal tibia articular joint circle (d). To test the second hypothesis, we used CAD software to create schematic diagrams on which lateral radiographs of the ankle joint were not parallel (d  = 1, 2, 3, 4 mm). Five experienced ankle surgeons were asked to judge whether the ankle articular surfaces were parallel. Intraobserver reliability was determined using the intraclass correlation coefficients (ICCs) and interobserver agreement by the Kendall coefficient of concordance. Results First, the intraobserver reliability was high (Cronbach's alpha >0.80) with regard to radiographic measurements according to the ICC. Significant interobserver disagreement was found (Kendall tauB, p  < 0.01) using the Kendall concordance coefficient. Second, when thed -value was 4 mm, all the observers identified the incongruous ankle joint at two separate times. Conclusions Consultation with experienced foot and ankle surgeons and precise definitions for lateral measurement assessments do not guarantee a high level of agreement. Surgeons can observe an incongruous ankle joint on lateral radiographs when thed -value is 4 mm.